Co-digestion of the organic fraction of municipal solid waste and sludge improves the energy balance of wastewater treatment plants: Rovereto case study. (December 2017) - Mattioli, A.; Gatti, G.B.; Mattuzzi, G.P.; Cecchi, F.; Bolzonella, D.
Abstract: The effects of co-digestion of separately collected organic fraction of municipal solid waste and mixed sludge in a 95, 000 equivalent inhabitants municipal wastewater treatment plant (WWTP) was studied for 18 months. It was observed that the treatment of 10, 000 kg per day of organic waste increased the organic loading rate of digesters from 0.73 to 1.38 kgVS per m 3 per day and allowed for a substantial increase in biogas generation from 1321 to 2723 m 3 /d (average data) determining a clear increase in energy recovery: potential power generation passed from 3900 kWh per day (only sludge treated) to 7800 kWh per day (co-digestion regime) or 85% of the total energy consumption of the wastewater treatment plant. Highlights: 10 tons per day of organic waste were co-digested with sludge in a wastewater treatment plant. The organic loading rate doubled without any process upset. Biogas production increased from 1321 to 2723 m 3 /d. The produced energy passed from 4000 to 8100 kWh per day. Up to 85% of the energy demand was covered by power self-production.